2014
DOI: 10.1007/s10439-014-1033-5
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Vascular Endothelial Cell eNOS and ET-1 Expression Induced by Laminar Shear Stress in an Ex Vivo Perfused System

Abstract: Vascular endothelial cell function responds to steady laminar shear stress; however, the underlying mechanisms are not fully elucidated. In the present study, we examined the effect of steady laminar shear stress on vascular endothelial cell autophagy and endothelial cell nitric oxide synthase (eNOS) and endothelin-1 (ET-1) expression using an ex vivo perfusion system. Human vascular endothelial cells and common arteries of New Zealand rabbits were pretreated with or without rapamycin or 3-MA for 30 min. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 32 publications
6
62
0
Order By: Relevance
“…In contrast, pretreatment of rapamycin enhanced the expression of eNOS under laminar shear stress. 38 Acute treatment of a mouse model of Alzheimer's disease with rapamycin activated eNOS and NO production in the brain endothelium and preserved vascular density. 39 The apparent discrepancy suggests that rapamycin may initiate a different response under different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pretreatment of rapamycin enhanced the expression of eNOS under laminar shear stress. 38 Acute treatment of a mouse model of Alzheimer's disease with rapamycin activated eNOS and NO production in the brain endothelium and preserved vascular density. 39 The apparent discrepancy suggests that rapamycin may initiate a different response under different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…When pretreated with 3-methyladenine, endothelial NO synthase expression in ECs is inhibited and endothelin-1 expression is restored. 40 Overall, we may conclude that autophagy is a key cellular process in ECs that preserves endothelial function and prevents cardiovascular disease.…”
Section: Autophagy Preserves Endothelial Functionmentioning
confidence: 91%
“…It was recently reported that autophagy is activated when cultured ECs or isolated rabbit carotid arteries were exposed to SS compared to static conditions. 43 Interestingly, pretreatment with the autophagy inducer rapamycin followed by SS enhanced the shear-induced eNOS expression suggesting that autophagy may potentiate the beneficial effects of SS on the endothelium. 43 However, in the context of RP, the role of autophagy in EC survival and, in particular, the effect of shear stress on autophagy are unknown.…”
Section: Autophagy and Mitophagy - Regulation By Rosmentioning
confidence: 99%